Inquiry Co-Operation Model: An Effort to Enhance Students’ Mathematical Literacy Proficiency - Malasari, Putri Nur; Herman, Tatang; Jupri, Al (JTAM (Jurnal Teori dan Aplikasi Matematika), 2020)
The urgency and proficiency of students’ mathematical literacy in Bandung that have not been optimal are the basis of this study. The aim of this study is to explain the enhancement of students' mathematical literacy proficiency due to the implementation of the inquiry co-operation model (experimental class) and conventional learning (control class) in terms of basic mathematical proficiency. This study is a quasi-experimental study with a non-equivalent control group design, and the research subjects were seventy students of class VIII of Bandung that were selected through a purposive sampling technique. The research data was obtained through mathematical literacy tests of material in a polyhedron. The results of the data analysis showed that: (1) the enhancement in mathematical literacy proficiency of the experimental students class was better than the control studentsclass in terms of the basic mathematical proficiency (high and medium); (2) there is no significant difference in the increase of mathematical literacy proficiency in experimental students class in terms of the basic mathematical proficiency. It can be concluded that inquiry co-operation model espouses the enhancement of students' mathematical literacy proficiency.